Historical Empathy: Judging the People of the Past in a Secondary Social Studies Classroom (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Historical empathy is a structural element of the study of history that needs to be taught in every secondary history classroom. It is important not only for the sake of accuracy in our studies, but also because helping students develop historical empathy has been proven to help improve their historical understanding and increase their interest in the study of history. Instructional strategies like reading and interpreting primary sources, role-playing, and engaging in writing that requires empathetic understanding have been found to be the most beneficial in fostering historical empathy in the classroom. It is also imperative to teach students how to engage in historical empathy in order that they can more accurately interpret history and judge the people of the past more fairly.